2021
DOI: 10.1007/s10098-021-02082-3
|View full text |Cite
|
Sign up to set email alerts
|

Integration of low-grade heat from exhaust gases into energy system of the enterprise

Abstract: In the paper is presented the way of Process Integration application for waste heat utilisation from exhaust gases streams with partial condensation. It is based on the construction of Hot Composite Curve representing the gaseous mixture cooling with accounting for the gas-liquid equilibrium of condensable vapour part. With Cold Composite Curve for streams requiring heating, the Pinch Point is determined. Then the structure of Heat Exchanger Network (HEN) for utilised Heat Integration into the energy system of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Process integration with the use of efficient PHEs for a carbon dioxide post-combustion capture unit HEN [145] enabled a decrease in energy consumption by 24% compared to the decrease of 11% that could be obtained with the use of shell-and-tube heat exchangers, with over 10% lower investment costs. Process integration with the use of PHEs for waste heat recovery from exhaust gas streams at tobacco factories [146] resulted in a decrease in carbon dioxide emissions by 600 t/y, with a payback period of about four months. The importance of using PHEs in the development and retrofitting of HENs for different industries was emphasised by Li et al [147] and shown through practical examples of HEN retrofitting with a detailed PHE design in [13].…”
Section: Phes In Various Applications As Individual Units and In Heat...mentioning
confidence: 99%
“…Process integration with the use of efficient PHEs for a carbon dioxide post-combustion capture unit HEN [145] enabled a decrease in energy consumption by 24% compared to the decrease of 11% that could be obtained with the use of shell-and-tube heat exchangers, with over 10% lower investment costs. Process integration with the use of PHEs for waste heat recovery from exhaust gas streams at tobacco factories [146] resulted in a decrease in carbon dioxide emissions by 600 t/y, with a payback period of about four months. The importance of using PHEs in the development and retrofitting of HENs for different industries was emphasised by Li et al [147] and shown through practical examples of HEN retrofitting with a detailed PHE design in [13].…”
Section: Phes In Various Applications As Individual Units and In Heat...mentioning
confidence: 99%